Dampak pengembangan pantai dengan kearifan lokal dalam meningkatkan pendapatan masyarakat sekitar - Alpinda, Piyo (Universitas Negeri Surabaya, 2023)
Tourism is seen as an important sector in the development of the world economy. Village tourism is one form of implementation of community-based and sustainable tourism development as a generator of regional economic growth, and as a poverty alleviation tool. This research aims to analyze the impact of beach development with local wisdom in increasing the income of the surrounding community (case study on Sebalang beach Kalianda South Lampung). The type of research used is qualitative research with data analysis techniques through observation, interviews, questionnaires, documentation, and data analysis. The results of the analysis show that in the development of Sebalang beach, local wisdom values are the main capital in building human creativity that has economic value and can increase people's income without damaging the social order and the surrounding natural environment.